2007
DOI: 10.1002/ijc.22797
|View full text |Cite
|
Sign up to set email alerts
|

Introducing α(1,2)‐linked fucose into hepatocarcinoma cells inhibits vasculogenesis and tumor growth

Abstract: The glycoantigen sialyl-Lewis x (sLex) and its isomer sialy-Lewis a (sLea) are frequently associated with advanced states of cancer and metastasis. In a previous work, we have shown that hepatocarcinoma cells (HCC) HepG2 interact with the endothelial Eselectin exclusively through sLe x oligosaccharides, the synthesis of which could be completely prevented by the a(1,2)-fucosyltransferase-I (FUT1), thus resulting in a strong inhibition of adhesion and rolling on activated endothelial cells. The purpose of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…Mathieu et al reported that tumor vascularization was decreased after FUT1 inhibition (44), and supported the findings of Palumberi et al, who showed that adhesion of human epidermoid carcinoma cells to FUT1 and FUT2 small interfering RNA (siRNA)-transfected ECs was decreased compared to control siRNAtransfected ECs. These investigators also reported that FUT1 and FUT2 siRNA-treated human epidermoid carcinoma cells have reduced cell proliferation when transfected with FUT1 or FUT2 siRNA (45).…”
Section: Discussionsupporting
confidence: 59%
“…Mathieu et al reported that tumor vascularization was decreased after FUT1 inhibition (44), and supported the findings of Palumberi et al, who showed that adhesion of human epidermoid carcinoma cells to FUT1 and FUT2 small interfering RNA (siRNA)-transfected ECs was decreased compared to control siRNAtransfected ECs. These investigators also reported that FUT1 and FUT2 siRNA-treated human epidermoid carcinoma cells have reduced cell proliferation when transfected with FUT1 or FUT2 siRNA (45).…”
Section: Discussionsupporting
confidence: 59%
“…This is in agreement with Mathieu et al . who showed that fut1-deficient hepatocarcinoma cells had reduced angiogenic responses [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that introduction of Fut1 into human cancer cells inhibits vasculogenesis, tumour growth and metastasis,28 29 while others found that Fut1 plays an active role in angiogenesis, tumour growth, and metastasis 5 8. To resolve this issue, we performed a number of angiogenesis assays by employing Fut1 −/− ECs and Fut1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%